Laser photobiomodulation effect on fibroblasts viability exposed to endodontic medications - Gustavo Danilo Nascimento Lima; Luiz Alexandre Chisini; Marcus Cristian Muniz Conde; André Luís Faria e Silva; Flávio Fernando Demarco; Maria Amália Gonzaga Ribeiro (Universidade Estadual de Campinas, 2021)
Aim: The literature has not yet reported investigations about the effect of laser photobiomodulation (LPBM) over the cytotoxicity of drugs for endodontic treatments. Thus, the aim of this study was to evaluate, in vitro, the effect of the association between LPBM and intracanal medications on fibroblasts viability in different exposure times. Methods: Calcium hydroxide (Ca(OH)2) and iodoform (IO) were used pure or associated to LPBM. Eluates of medications were prepared and placed in contact with the cells in three different periods: 24h, 48h and 72h. Laser irradiation (emitting radiation λ 660nm, power density of 10mW, energy density of 3 J/cm²) has been performed in two sessions within a six hour interval, for 12s per well. After each experimental time, the colorimetric assay (MTT) has been performed. Statistical analysis was applied for Mann-Whitney test with 5% α error admitted test. Results: At 24h, the use of LPBM did not increase cell viability while after 72h cell proliferation was stimulated in the group without medications. LPBM application did not increase cell viability in Ca(OH)2 group and IO at any tested time. Ca(OH)2 cytotoxicity at 24h was higher than iodoform, while at 72h not difference was observed. Therefore, after 72 hours was no statistical difference between the IO and Ca(OH)2 groups. Conclusion: LPBM was able to increase cell viability in 72h in the group without medication, although no improvement was observed in the other groups. Thus, LPBM was not able to reduce the cytotoxic effects of the materials on fibroblasts in vitro.